CleanEra - A Collection of Research Projects for Sustainable Aviation - The CleanEra Team (IOS Press, 2015)
The CleanEra project was initiated with the goal of developing revolutionary ideas for civil aviation. These ideas were to offer solutions which would limit and reduce some of the negative aspects of aviation, namely: emissions and the use of resources. This book presents you with the highlights of this journey in search of new technologies for a revolutionary aircraft; an aircraft that not only offers a future of comfortable air travel for the passenger, but a future of sustainable aviation for the planet as well.